Συστηματικός Σχεδιασμός, Ανάπτυξη και Αξιολόγηση Παιχνιδοποιημένων Περιβαλλόντων Εκμάθησης - (:unkn) unknown (My University, 2022)
Η παρούσα διατριβή έχει ως στόχο την επικύρωση της θεωρίας μάθησης του κονστρουκτιβισμού και να αποδώσει τις πιθανές συστηματικές προσεγγίσεις που επιτρέπουν στις προκλήσεις Capture the Flag (CTF) και στα Cyber Ranges να παρέχουν σημαντικό μαθησιακό αντίκτυπο. Η παρούσα έρευνα συμβάλει στην κατανόηση σχετικά με τον σχεδιασμό της έρευνας και τη μεθοδολογική ανάπτυξη που απαιτείται για την ενίσχυση του μαθησιακού αντίκτυπου των προκλήσεων CTF και των Cyber Ranges ως εικονικών περιβαλλόντων μάθησης στον κυβερνοχώρο. Ο πειραματικός σχεδιασμός στηρίζεται μεθοδολογικά στο Action Design Research (ADR) και αξιοποιήθηκε για την παροχή δεδομένων σχετικά με τον σχεδιασμό και την ανάπτυξη ψηφιακών περιβαλλόντων εκμάθησης στην κυβερνοασφάλεια. Στην έρευνα συμπεριλαμβάνεται κριτική αξιολόγηση των περιβαλλόντων μάθησης στον κυβερνοχώρο λαμβάνοντας υπόψη τις έννοιες της παιχνιδοποίησης (gamification) και της μάθησης που βασίζεται σε παιχνίδι (Game-Based Learning). Η έρευνα παρέχει τη βάση για έναν νέο τρόπο σχεδίασης και ανάπτυξης περιβαλλόντων μάθησης στον κυβερνοχώρο και τη δημιουργία συναφών σεναρίων στην κυβερνοασφάλεια ως βάσης για την απόκτηση τεχνικών δεξιοτήτων στον τομέα της πληροφορικής.

This research aims to validate the learning theory of constructivism and identify the possible systematic approaches to design, deploy, and evaluate cybersecurity learning environments using Capture the Flag (CTF) challenges and Cyber Ranges to provide a significant learning impact. Capture the Flag (CTF) challenges and Cyber Ranges are among the most widely used approaches to provide technical exercises in cybersecurity, mostly as an assessment method to evaluate skills. Despite interest in CTF challenges and Cyber Ranges, few studies have considered systematic approaches to relate technical exercises to the cybersecurity curriculum. Furthermore, research on gamification or game-based learning in cybersecurity has not included these approaches until now. This research contributes to understanding of the design and methodological development to improve approaches, including but not limited to CTF challenges and Cyber Ranges. The research is methodologically based on Action Design Research (ADR) that is used to provide empirical data on the design and development of digital cybersecurity learning environments. Furthermore, the scope of research of this thesis includes a critical evaluation of cyber learning environments, taking into account the concepts of gamification and game-based learning within the scope of this research. This research provides the foundation for a new method to design, develop, and deploy cybersecurity learning environments and related cybersecurity scenarios, as a baseline to acquire technical skills in IT.
Systematic Design, Deployment and Evaluation of Gamified Cybersecurity Learning Environments
Keywords: Κυβερνοασφάλεια, Ασφάλεια πληροφοριακών συστημάτων, Εκπαίδευση στην Κυβερνοασφάλεια, Μάθηση βασισμένη στα ψηφιακά παιχνίδια, Σοβαρά Παιχνίδια, Παιχνιδοποίηση, Κοινωνικός κονστρουκτιβισμός, Μάθηση με βάση το ψηφιακό παιχνίδι; Cybersecurity, Information Security, Cybersecurity Education, Digital Game-Based Learning, Serious Games, Social Constructivism, Cyber Ranges, Capture the Flag Challenges